Strengthening Global Fire Safety Governance: Examining Integrity and Accountability Measures in Bureau of Fire Protection Bacnotan La Union - Fajardo, Maribel B.; Miguel, Laurence B.; Bagona, Judith M. (Future Science / FSH-PH Publications, 2025)
This study evaluates the integrity and accountability mechanisms of the Bureau of Fire Protection (BFP) in Bacnotan, La Union. Using a quantitative approach, data were collected through a validated and pilot-tested survey instrument distributed to 90 stakeholders, including barangay officials, community members, and business sector representatives. Descriptive statistics and ANOVA were used to assess stakeholder perceptions across six governance dimensions: code of conduct, transparency, responsiveness, anti-corruption, public engagement, and performance review. Results indicated generally favorable perceptions, with the business sector reporting the highest satisfaction. However, relatively lower scores in anti-corruption suggest areas for improvement. The study highlights the importance of ethical leadership, community engagement, and transparency in public safety governance. Recommendations include enhancing feedback mechanisms, reinforcing anti-corruption initiatives, and scaling best practices across other regions.